From Screening to Targeted Degradation: Strategies for the Discovery and Optimization of Small Molecule Ligands for PCSK9. Issue 1 (16th January 2020) - Petrilli, Whitney L.; Adam, Gregory C.; Erdmann, Roman S.; Abeywickrema, Pravien; Agnani, Vijayalakshmi; Ai, Xi; Baysarowich, Jen; Byrne, Noel; Caldwell, John P.; Chang, Wonsuk; DiNunzio, Edward; Feng, Zhe; et al.
Summary: Proprotein convertase substilisin-like/kexin type 9 (PCSK9) is a serine protease involved in a protein-protein interaction with the low-density lipoprotein (LDL) receptor that has both human genetic and clinical validation. Blocking this protein-protein interaction prevents LDL receptor degradation and thereby decreases LDL cholesterol levels. Our pursuit of small-molecule direct binders for this difficult to drug PPI target utilized affinity selection/mass spectrometry, which identified one confirmed hit compound. An X-ray crystal structure revealed that this compound was binding in an unprecedented allosteric pocket located between the catalytic and C-terminal domain. Optimization of this initial hit, using two distinct strategies, led to compounds with high binding affinity to PCSK9. Direct target engagement was demonstrated in the cell lysate with a cellular thermal shift assay. Finally, ligand-induced protein degradation was shown with a proteasome recruiting tag attached to the high-affinity allosteric ligand for PCSK9. Graphical Abstract: Highlights: Unprecedented allosteric small-molecule binder to PCSK9 was identified using AS/MS Biased and unbiased hit-to-lead strategy identified binders through divergent SAR Demonstrated binding of lead compound to PCSK9 in a cellular thermal shift assay Developed lead compound into targeted degrader achieving 60% reduction of PCSK9 levels Abstract : Petrilli et al. describe the identification of high-affinity small-molecule binders to PCSK9 through two complementary hit-to-lead approaches. The lead compound was shown to bind to PCSK9 in a cellular thermal shift assay and subsequently developed into a targeted protein degrader.